Service quality evaluation: an analysis of the students perception of a higher education institution - Silva, Sthéfany Marilac (2019)
In Brazil, the 2000’s were marked by the reconstruction of higher education, which resulted in a considerable growth of educational institutions in both the public and private sectors. In this context, a challenge was emerged to evaluate and monitor the performance of these institutions. Thus, this study aims to identify the gaps between the expectations and perceptions of the students in a Public Institution of Higher Education in relation to the quality of services provided. In order to meet this objective, the research method adopted was that of a data collection survey. As a tool for analysis, a questionnaire based on the ServQual scale was used, which allowed to infer five aspects related to the services (tangibility, responsiveness, reliability, assurance and empathy). The analysis was carried out in the Research, Extension, Administrative and Teaching Departments of the institution. As for the main results, it was observed that the Tangibility aspect obtained the best evaluation in all sectors while the Reliability aspect was the one that presented the highest negative Gap. The results permitted the identification of opportunities of betterment for each of the sectors analyzed.